2018
DOI: 10.1016/j.anr.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Iranian Nursing Students Regarding Their Clinical Learning Environment

Abstract: Findings showed that the CLE of Iranian nursing students may be inadequate for high-level learning and safe and effective teaching. Addressing these challenges will require academic and practice partnerships to examine the systems affecting the CLE, and areas to be addressed are described in the six themes identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
0
27
1
5
Order By: Relevance
“…1 These academic and clinical stressors can be triggered by examination preparation, course workload, paying course fees, not meeting personal needs, heavy workload, taking care of patients, being criticized by teachers, encountering a dying patient, the fear of making practice errors and experiencing bullying and discrimination in clinical settings. [1][2][3][4] It has been demonstrated that nursing students use a variety of both adaptive and maladaptive coping strategies to manage these academic and clinical problems. 5 Particularly in relation to stress and coping, the psychological well-being of nursing students is an important focus of nurse education research.…”
mentioning
confidence: 99%
“…1 These academic and clinical stressors can be triggered by examination preparation, course workload, paying course fees, not meeting personal needs, heavy workload, taking care of patients, being criticized by teachers, encountering a dying patient, the fear of making practice errors and experiencing bullying and discrimination in clinical settings. [1][2][3][4] It has been demonstrated that nursing students use a variety of both adaptive and maladaptive coping strategies to manage these academic and clinical problems. 5 Particularly in relation to stress and coping, the psychological well-being of nursing students is an important focus of nurse education research.…”
mentioning
confidence: 99%
“…The trainees gain a sense of independence, considering that they are already engaged in their respective specializations, and enhanced supervision contributes to a more effective outcome, especially because the ANP diploma is new in the country [7]. Being unsure as to whom to approach for clarifications and/or being unable to receive a proper response hinder the trainees' achievement of diploma goals [15].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical placements have a significant impact on nursing students’ clinical learning and their preparation for the nursing profession [1]. Clinical placements aim to enhance students’ critical thinking and communication skills, integrate taught theory and skills into practice, and apply learned ethical principles in real-life settings to function as a member of the healthcare team [2]. Healthcare and education sectors have a joint responsibility to ensure that nursing graduates enter the nursing workforce with enough knowledge, clinical skills, and confidence to practice in dynamic clinical environments that involve high levels of patients’ acuity and nursing workloads.…”
Section: Introductionmentioning
confidence: 99%